Luces y sombras de la transformación militar aliada - Guillem Colom Piella (Revista Electrónica de Estudios Internacionales, 2012)
The article is aimed at analyzing the Allied military transformation from its beginnings in 2002 to the current day. Ten years after the launch of this ambitious initiative, the Allied military transformation is at a difficult crossroads: the process has lost its original guiding principles; it has not helped to bridge the gap between the divergent strategic cultures or to reduce the rising capability gap between both shores of the Atlantic; is has demonstrated its inability to respond to the operational challenges caused by the Allied campaign in Afghanistan; and the 2010 Strategic Concept does not provide a clear political guide to lead this process for the forthcoming years.